Estimating Ice Discharge at Greenland's Three Largest Outlet Glaciers Using Local Bedrock Uplift. Issue 14 (22nd July 2021) - Hansen, Karina; Truffer, Martin; Aschwanden, Andy; Mankoff, Kenneth; Bevis, Michael; Humbert, Angelika; van den Broeke, Michiel R.; Noël, Brice; Bjørk, Anders; Colgan, William; Kjær, Kurt H.; Adhikari, Surendra; et al.
Abstract: We present a novel method to estimate dynamic ice loss of Greenland's three largest outlet glaciers: Jakobshavn Isbræ, Kangerlussuaq Glacier, and Helheim Glacier. We use Global Navigation Satellite System (GNSS) stations attached to bedrock to measure elastic displacements of the solid Earth caused by dynamic thinning near the glacier terminus. When we compare our results with discharge, we find a time lag between glacier speedup/slowdown and onset of dynamic thinning/thickening. Our results show that dynamic thinning/thickening on Jakobshavn Isbræ occurs 0.87 ± 0.07 years before speedup/slowdown. This implies that using GNSS time series we are able to predict speedup/slowdown of Jakobshavn Isbræ by up to 10.4 months. For Kangerlussuaq Glacier the lag between thinning/thickening and speedup/slowdown is 0.37 ± 0.17 years (4.4 months). Our methodology and results could be important for studies that attempt to model and understand mechanisms controlling short‐term dynamic fluctuations of outlet glaciers in Greenland. Plain Language Summary: A wide range of sensors and methods have been used to study the changes of the Greenland Ice Sheet, including satellite gravimetry, altimetry, and the input‐output method. Here, we present a novel fourth method to estimate dynamic ice loss of Greenland's three largest outlet glaciers: Jakobshavn Isbræ, Kangerlussuaq Glacier, and Helheim Glacier. We use Global Navigation Satellite System (GNSS) stations attached to bedrock to measure rise of land masses caused by ongoing ice mass loss near the glacier terminus. When we compare our results with ice discharge, we find a time lag between glacier speedup/slowdown and onset of dynamic induced thinning/thickening. Our results show that dynamic thinning/thickening on Jakobshavn Isbræ occurs 0.87 ± 0.07 years before speedup/slowdown. This implies that using GNSS uplift time series we are able to predict ice flow speedup/slowdown of Jakobshavn Isbræ by up to 10 months. For Kangerlussuaq Glacier and Helheim Glacier the lag between thinning/thickening and speedup/slowdown is 0.37 ± 0.17 years (4.4 months) and 0.03 ± 0.16 years, respectively. Our methodology and results could be important for studies that attempt to model and understand mechanisms controlling short‐term dynamic fluctuations of outlet glaciers in Greenland. Key Points: A novel method to estimate dynamic ice loss of Greenland's three largest outlet glaciers, Jakobshavn, Kangerlussuaq, and Helheim glacier Dynamic thinning/thickening occurs 0.87 ± 0.07 years before speedup/slowdown at Jakobshavn Isbræ A similar time lag between change in uplift rate and flow speed change allows us to predict future ice discharge from past uplift